(untitled) (Research, Society and Development, 2019)
This is a case study research applied to Ineagro, a technology-based incubator for agribusiness enterprises at the Federal Rural University of Rio de Janeiro. The study aimed to verify the companies incubated and graduated by Ineagro. An interview was also held with the project coordinator of the incubator with the objective of understanding the work of Ineagro in the promotion of agribusiness startups and the challenges and innovations of the incubator. By means of the results it was possible to identify the areas of activity of the incubated companies and to perceive the main challenges and projects of the incubator. It was also possible to understand some aspects of the relationship between the incubator and the university where some difficulties were observed. In addition, companies with a consistent technological base were found, demonstrating the potential of the incubator located on the campus of a university of importance in the agribusiness research scenario and close to two research centers, Pesagro and Embrapa.